Entrepreneurial and social significance of larps: A case study of the Kuńkowce Fantasy Village - Sala, Krzysztof (Social Entrepreneurship Review, 2023)
Background: The author’s personal scientific interests and the existing research gap motivated him to pursue the topic. The article discusses the impact of larps on entrepreneurship and local communities. Research objectives: To analyse larp as a component of social and entrepreneurial engagement, with a special focus on its origins, definitions, and development paths based on a case study of the Kuńkowce Fantasy Village. Research design and methods: The research technique included a review of existing data, relevant literature, and a direct interview conducted in February 2023 with a purposively selected group of people involved in organising larps. Results: The research questions were intended to evaluate the impact of larps on local entrepreneurship and social initiatives. Conclusions: The findings permitted the author to identify the entrepreneurial and social dimensions of the Kuńkowce Fantasy Village as well as other larp projects pursued worldwide and in Poland.